Plastic Waste Management in North Macedonia: A Comparative Analysis With Western Balkans And Selected EU Countries - Ivanova, Ivana; Makrevska disoska, Elena (My University, 2024)
This paper aims to compare North Macedonia as an EU candidate country, to the Western Balkan countries in circular economy movements. It shows that the country still struggles with advancing circularity and is more focused on waste management practices, which also do not function well. Lack of waste separation, weight equipment, and qualitative waste data with limited access to funds, finance, and knowledge are possible reasons. Plastic as a future raw material which is gaining more attention at a global scale is not even a priority in the Macedonian economy. This paper gives for the first time a link between plastic waste and the circular economy in North Macedonia, highlighting the economic sectors and the role that EPR schemes are playing in increasing higher recycling rates, compared with other materials used for packaging. In the end, the authors compare the country with developed EU countries like Slovenia and Germany to examine the effects of higher communal fees would contribute to a more efficient municipal waste system, by using the municipal costs as a percentage of GDP per capita, minimal wage and Income and Living Conditions Indicator.
Keywords: Western Balkan; Municipal waste; Waste management; Circular Economy; European Union; Republic of North Macedonia; Plastic waste; Resource productivity